KAJIAN PENGARUH PENDIDIKAN SPIRITUALITAS TERHADAP EKSPRESI IMAN CALON GURU AGAMA KATOLIK DALAM MASYARAKAT MULTIKULTURAL DI INDONESIA - M. Pauline (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2020)
In the midst of the current situation in progress in all fields. The field of preaching the faith. also need to race and develop. A preacher of faith becomes salt and light as a sign of testimony to God's presence, especially in the midst of the times. Spiritual education is needed in such a way that shapes the personality of the reporter who influences the expression of his life of faith, especially in the multicultural society in Indonesia. In this study the author makes a study based on historical research, in the discussion the author explores from the history books of spiritual education by paying attention to the history of spirituality, spiritual figures, Church teachings on spirituality, about proclaiming faith, Christian education. knowing the challenges of spirituality education for prospective Catholic religious teachers, (2) The influence of spirituality education on the expression of life of faith, especially in the midst of multicultural society in Indonesia. This expression of faith is seen in individuals who enjoy prayer, individuals who want to renew their steps (repent), attitudes optimistic, trusting, courageous, independent (life attitude of a believer), steady, especially when facing temptations that go against the values ​​of his faith, able to be faithful, tough, not easy to follow negative currents, expression of love, patience, generosity, fear of Allah , prostrate to piety, missionary, cooperate and dialogue. The results found in this study spirituality education need to pay attention to several things An important aspect of the reporter's personality is related to the openness of the heart which is the center of the encounter with God, the area of ​​​​the mind, feelings and desires. In order to have an influence on the expression of life of faith, a person has intimacy with God, has inner freedom, is open to the work of the Holy Spirit in him, responds to said Allah. To achieve that, there were several ways that were found, namely related to increasing enthusiasm and skills in prayer, doing reflection and introspection activities. Gaining experience from holy figures and having dialogue with others, Knowing how to read and meditate on the scriptures.